2017
DOI: 10.2527/jas2017.1927
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of exposure of embryos produced in vitro in a serum-containing medium to dickkopf-related protein 1 and colony stimulating factor 2 on blastocyst yield, pregnancy rate, and birth weight1

Abstract: Embryokines are molecules secreted by the mother that regulate embryonic development. Among these molecules in cattle are colony stimulating factor 2 (CSF2) and dickkopf-related protein 1 (DKK1). Here, we evaluated actions of CSF2 and DKK1 alone or in combination on characteristics of embryos produced in vitro in the presence of serum. A total of 70 beef cows from 4 farms were subjected to oocyte retrieval on 1 to 4 occasions. Within each farm, donors were randomly allocated to 1 of 4 treatment groups (vehicle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 20 publications
0
29
0
1
Order By: Relevance
“…Indeed, there could be other aspects of development of the blastocyst not studied here, including downstream effects that occur much later in development, that could differ between female and male embryos. Embryokines like CSF2 [ 33 , 34 ] and DKK1 [ 35 ] can act on the preimplantation embryo to affect fetal and postnatal phenotypes. Despite the lack of difference on development to blastocyst stage, the observation that expression of three genes was affected by the IGF1 by sex interaction is indicative that IGF1 might exert sex-dependent actions affecting other aspects of embryo function besides development to the blastocyst stage (e.g., apoptosis, allocation of cells into specific lineages, epigenetic regulation, etc.).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there could be other aspects of development of the blastocyst not studied here, including downstream effects that occur much later in development, that could differ between female and male embryos. Embryokines like CSF2 [ 33 , 34 ] and DKK1 [ 35 ] can act on the preimplantation embryo to affect fetal and postnatal phenotypes. Despite the lack of difference on development to blastocyst stage, the observation that expression of three genes was affected by the IGF1 by sex interaction is indicative that IGF1 might exert sex-dependent actions affecting other aspects of embryo function besides development to the blastocyst stage (e.g., apoptosis, allocation of cells into specific lineages, epigenetic regulation, etc.).…”
Section: Discussionmentioning
confidence: 99%
“…Supplementing DKK1 during IVP embryo culture appears beneficial to calving outcomes. Increases in blastocyst development and pregnancy retention occurred in DKK1 treated IVP embryos in one study lacking serum in culture medium (Denicol et al, 2014), but not in another study that utilized a serum-containing medium ( Tríbulo et al, 2017). In the latter study, a reduction in birth weights was observed in calves from DKK1-exposed IVP embryos (Tríbulo et al, 2017).…”
Section: Recent Attempts To Improve Ivp Embryo Competencymentioning
confidence: 87%
“…Increases in blastocyst development and pregnancy retention occurred in DKK1 treated IVP embryos in one study lacking serum in culture medium (Denicol et al, 2014), but not in another study that utilized a serum-containing medium ( Tríbulo et al, 2017). In the latter study, a reduction in birth weights was observed in calves from DKK1-exposed IVP embryos (Tríbulo et al, 2017). The mechanism responsible for this outcome is unclear, but this finding may have important implications for further reducing the incidence of large offspring syndrome in IVP pregnancies.…”
Section: Recent Attempts To Improve Ivp Embryo Competencymentioning
confidence: 91%
See 1 more Smart Citation
“…One possible mediator of the effects of progesterone on embryonic elongation in the ruminant is DKK1, an endogenous modulator of WNT signaling produced by the endometrium 22 . Addition of DKK1 to culture medium improves the ability of bovine embryos to establish and maintain pregnancy after transfer 23 and affects birthweight of offspring 24 . Endometrial expression of DKK1 is induced by progesterone in the cow 3 , sheep 25 and human 26,27 .…”
Section: Introductionmentioning
confidence: 99%